Using a choice experiment to determine tourist preference heterogeneity for beach recreational attributes at Port Dickson, Malaysia - W. Mohamad, Wan Norhidayah; Samdin, Zaiton; Basri, Bakti Hasan (Inderscience Enterprises Ltd., 2023)
Beaches have high economic value due to visitors leisure goods and services demand. However, beach recreational resources are anticipated to face pressure and trade-offs due to restricted local government funding. Port Dickson in Malaysia comprises a length of coastline where recreational opportunities are being imperilled by increased tourist demand. This study determined tourists key preferences for beach recreational attributes in Malaysia to inform policymakers when making decisions regarding the coastal allocation of funds. Choice experiment (CE) estimations were made using mixed logit (MXL) simple and interaction models. Four attributes were involved; amenities, recreational facilities, cleanliness and entrance fees. The results revealed that tourists were willing to pay MYR1.895 to MYR4.22 for a high level of recreational facilities, cleanliness of the water and beach, and amenities provided at the beach. The findings also revealed that; age, gender and education all significantly impacted tourists preferences.